2019
DOI: 10.1037/emo0000431
|View full text |Cite
|
Sign up to set email alerts
|

The semantics of emotion in false memory.

Abstract: The emotional valence of target information has been a centerpiece of recent false memory research, but in most experiments, it has been confounded with emotional arousal. We sought to clarify the results of such research by identifying a shared mathematical relation between valence and arousal ratings in commonly administered normed materials. That relation was then used to (a) decide whether arousal as well as valence influences false memory when they are confounded and to (b) determine whether semantic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Valence-arousal relations can differ for positive versus negative items (Kuppens et al, 2013). For instance, Brainerd and Bookbinder (2018) and Citron, Weekes, and Ferstyle (2014) reported that the best-fitting quadratic functions for the relation between bipolar valence and arousal judgments about selected pools of words were asymmetrical. Specifically, unit changes in valence on the negative sides of valence scales produced larger changes in arousal than did unit changes on the positive sides, and hence, the average level of arousal associated with a given valence value on the negative side was higher than for the corresponding value on the positive side.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Valence-arousal relations can differ for positive versus negative items (Kuppens et al, 2013). For instance, Brainerd and Bookbinder (2018) and Citron, Weekes, and Ferstyle (2014) reported that the best-fitting quadratic functions for the relation between bipolar valence and arousal judgments about selected pools of words were asymmetrical. Specifically, unit changes in valence on the negative sides of valence scales produced larger changes in arousal than did unit changes on the positive sides, and hence, the average level of arousal associated with a given valence value on the negative side was higher than for the corresponding value on the positive side.…”
Section: Resultsmentioning
confidence: 99%
“…Best-fitting regression equations for the relation between emotional ambiguity and the valence–arousal correlation for the (a) negative and (b) positive subfiles of the Toglia-Battig-emotional database (Brainerd & Bookbinder, 2018). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One states that emotion inoculates memory against distortion and that when emotion becomes intense, it is virtually impossible to develop false memories of events (Laney & Loftus, 2010). But the other states opposite—that emotion foments false memories, with distortion increasing as emotion intensifies (Brainerd & Bookbinder, in press).…”
Section: Introductionmentioning
confidence: 99%